The Role of Nitrosative Stress and Endothelial Dysfunction in the Development of Pneumonia in Patients with Ischemic Stroke - Khurshidakhon Abduboriyevna, Rasulova; Itolmas Hamroevich, Achilov (International Journal of Psychosocial Rehabilitation, 2020)
In 78 patients with pneumonia (average age 59 ± 7 years), the levels of endothelin-1 (ET-1), nitrite and nitrate anions (NO₂⁻ and NO₃⁻), and 3-nitrotyrosine (3-NO-Tyr) in the blood serum were determined. Of these, the first (main) group included 41 patients with pneumonia who had a history of ischemic stroke (IS) for more than six months (P + IS); the second group (comparisons) was 37 with a history of pneumonia without a stroke (P). The control group consisted of 20 relatively healthy donors, comparable in age and gender with the studied groups. In all patients, the severity of the symptoms of pneumonia was evaluated, and the data of clinical, laboratory, and instrumental research methods were analyzed. The content of NO2- and NO3- in the selected and frozen blood sera of patients was determined using the Griss reagent (Reakhim, Russia) spectrophotometrically; the content of 3-NO-Tyr was determined spectrophotometrically by the reaction with hydrochloric acid, estimating the maximum light absorption at a wavelength of 370 nm; and the level of ET-1 (1-21) was determined by enzyme-linked immunosorbent assay using a commercial set of Biomedica (Austria). In patients with P + IS, compared with patients with P without a history of stroke, the symptoms of the disease were more pronounced due to the more severe course of pneumonia. All patients included in the study revealed a significant decrease in the content of NO₂⁻ and NO₃⁻ in the blood, as well as a significant increase in the concentration of 3-NO-Tyr, which indicated a violation of the metabolism of nitric oxide (NO). Serum ET-1 was significantly higher than control values. In the blood, these changes were more pronounced in patients with P + IS. Indicators of NO metabolism had a correlation with the state of lung function and serum ET-1 content. Thus, the course of the disease in patients with P + IS and in patients with P without stroke is characterized by the development of nitrosative stress and endothelial dysfunction. Their intensity is more pronounced in patients with P + IS. The high frequency of changes in the levels of the studied parameters in patients with pneumonia, as well as in the case of transferred ischemic stroke, suggests the role of endothelial dysfunction and nitrosative stress in the development and worsening of pneumonia. The study of markers of endothelial dysfunction and nitrosative stress (ET-1, NO metabolites, 3-NO-Tyr) in patients with pneumonia provides additional information on the state of the inflammatory process and the effectiveness of the treatment, taking into account extrapulmonary comorbid conditions.